A novel infrared and microwave alternate thawing method for frozen pork: Effect on thawing rate and products quality. (April 2023) - Hu, Rui; Zhang, Min; Jiang, Qiyong; Law, Chung Lim
Abstract: The effect of infrared and microwave alternate thawing (IR + MWT) on frozen pork were compared to fresh, air thawing (AT), infrared thawing (IRT), microwave thawing (MWT). The IR + MWT took only about 11.81 min of the thawing time compared to AT 66.5 min, and the Raman spectroscopy and Low-field nuclear magnetic resonance (LF-NMR) results showed that the IR + MWT maintained better protein secondary structure composition and moisture state compared to MWT and IRT. In terms of thawing losses, IR + MWT had the lowest loss 1.92%. In terms of texture, IR + MWT had the least effect on the post-thawing textural properties and increased the springiness of the meat. Scanning electron microscopy results also showed that there was reduced damage to the muscle structure with IR + MWT. Regarding the odor of the meat after thawing, IR + MWT retained the odor better and was closer to the fresh sample. Therefore, IR + MWT can be used to enhance the thawing rate to protect the quality of the thawed pork.